2021
DOI: 10.4236/ojbm.2021.91023
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Determinants of Financial Assistance and Credit Accessibility of Small and Medium-Enterprises (SME’s): A Case Study of SME’s in Takoradi Metropolis in the Western Region of Ghana

Abstract: In Ghana and other countries' economies, small and medium scale enterprises (SME's) play a principal role that significantly impacts economic stability. SMEs contribute prominently to the economy by creating more noteworthy work openings, making higher creation volumes, growing conveys and introducing progression and business capacities. This study used a sample of 336 SMEs out of 500 SME's located in the Western Region (Takoradi Metropolis). These SMEs data were obtained using questionnaire in which its instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…By examining the interactions between the environment, the economy, and sustainable development, this study intends to give insight on the complexities of achieving environmental sustainability in key sectors (Ahakwa et al, 2023; Ahmed et al, 2022; Xu & Li, 2020). Prior studies have demonstrated that this sampling methodology is accurate and provides reliable outcomes (Cobbinah et al, 2020; Kir et al, 2021; Owusu et al, 2022; Sappor et al, 2023; F. A. Sarpong et al, 2022, 2023).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By examining the interactions between the environment, the economy, and sustainable development, this study intends to give insight on the complexities of achieving environmental sustainability in key sectors (Ahakwa et al, 2023; Ahmed et al, 2022; Xu & Li, 2020). Prior studies have demonstrated that this sampling methodology is accurate and provides reliable outcomes (Cobbinah et al, 2020; Kir et al, 2021; Owusu et al, 2022; Sappor et al, 2023; F. A. Sarpong et al, 2022, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Using t-statistics and path coefficient values, bootstrapping was applied to evaluate the relevance of the linkages between model components and the strength of associations between these structures. For a t-statistic to be considered significant, it should exceed the threshold of 1.96 (Chin et al, 2018). Our analysis incorporated multiple evaluation metrics, including adjusted R2, Q2, and F2, to assess the effectiveness and accuracy of our proposed models.…”
Section: Structural Model Fitnessmentioning
confidence: 99%